A comparison between the efficacy and complication of laparoscopic and microsurgical varicocelectomy: Systematic review and meta-analysis - Syah Mirsya Warli; Rizky An Nabil; Dhirajaya Dharma Kadar; Fauriski Febrian Prapiska; Ginanda Putra Siregar (Urology Annals, 2024)
Varicocele is the dilatation of the scrotal veins and may affect sperm count and infertility. It is caused by congenital vein insufficiency or absence of venous valve. The main treatment is by surgery, and currently, there are two minimally invasive choices: laparoscopic and microsurgical varicocelectomy. This systematic review aimed to record randomized clinical trials from various sources using all qualified studies up to June 2022. The assessed outcomes were operation time, hydrocele, hospital stay, change in semen parameter, recurrence rate, and pregnancy rate. The essential data extracted were Jadad score, publication year, age, and sample size. This systematic review consisted of 509 and 512 patients in the laparoscopic and microsurgery group, respectively, taken from 12 out of 281 studies. The result of this systematic review was significant difference in operation time between patients from two groups (weighted mean difference [WMD] −21.40, 95% confidence interval [CI]: −28.90–−13.89); length of hospitalization (WMD: 0.38, 95% CI: 0.02–0.74); laparoscopic could significantly increase the risk of hydrocele by 3.30-fold (risk ratio [RR]: 3.30, 95% CI: 1.07–10.12); laparoscopic could significantly increase the recurrence rate by 6.98-fold (RR: 6.98, 95% CI: 3.46–14.08); no significant difference in spontaneous pregnancy between patients in both groups (RR: 0.81, 95% CI: 0.57–1.16); and laparoscopic surgery decreased the occurrence of sperm parameter changes by 40% (RR = 0.40, 95% CI: 0.25–0.62).